The Medieval Iberian Treasury in the Context of Cultural Interchange (Expanded Edition) - Martin, Therese (Brill, 2020)
The Medieval Iberian Treasury in the Context of Cultural Interchange-expanded beyond the special issue of Medieval Encounters from which it was drawn-centers on the magnificent treasury of San Isidoro de León to address wider questions about the meanings of cross-cultural luxury goods in royal-ecclesiastical settings during the central Middle Ages. Now fully open access and with an updated introduction to ongoing research, an additional chapter, composite bibliographies, and indices, this multidisciplinary volume opens fresh ways into the investigation of medieval objects and textiles through historical, art historical, and technical analyses. Carbon-14 dating, iconography, and social history are among the methods applied to material and textual evidence, together shining new light on the display of rulership in medieval Iberia. Readership: From students to advanced specialists interested in medieval history, art history, women's history, social history, rulership, material culture, Muslim-Christian interchange, Viking art, Iberia during the central Middle Ages.